Emerging as the 'Victor'(?): Syria and Russia's Grand and Military Strategies. Issue 1 (2nd January 2021) - Miron, Marina; Thornton, Rod
ABSTRACT: The war in Syria, given its complexity and geopolitical importance, has received much recent analytical attention. Although many perspectives have been covered, there is still a need in Western sources to view the conflict more through Russia's lens. This article thus looks at how Russia has designed and executed its military strategy in Syria to fit into its overall grand strategy. It examines exactly how the Russian 'strategy of limited actions' has been employed and why Russia has now been proclaimed as the one true 'victor' in the whole Syrian imbroglio.